BOOSTING EARLY CHILDHOOD LEARNING ENTHUSIASM AT RANGGI LITERACY HOME - Siregar, Ameilia Zuliyanti (Charity : Jurnal Pengabdian Masyarakat, 2025)
The Independent Student Exchange Program (PMM) 2024 is an activity launched by the Ministry of Education, Culture, Research and Technology. One of the important components in PMM is the Nusantara Module, which is designed to provide students with direct experience of cultural diversity in various regions in Indonesia, especially in North of Sumatra. This program aims to improve students' hard skills and soft skills through various activities. University of Sumatera Utara accepted 189 students from 82 universities in PMM 2024. Boosting Early Childhood Learning Enthusiasm at Ranggi Literacy Home will take place in Sampali, PWI Street, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra, on June 15-16, 2024, which involve 20 young children as participants. The event started at 1:00 PM to 2:00 PM on the first day, where children engaged in coloring activities. On the second day, from 10:00 AM to 2:00 PM, the activities included reading, counting activities, arranging syllabus, making toys from recycled materials, and hand washing. Assessment activities will be conducted to monitor the children's progress in understanding the taught materials. A final evaluation will assess the achievement of activity objectives and their impact on the early childhood learning enthusiasm in the Ranggi literacy community with 10 questions, consist of: 50% happy when the older siblings come and introduce themselves; 50% like coloring with paper and colored pencils; 67% like colouring by colouring pencils, 72% dislike syllable cards; 78% like coloring with paper and colored pencils; 67% counting illustrated paper; 61% like coloring with paper and colored pencils; 78% making toy cars from recycled items; 50% playing the toys; and 50% making toy cars from recycled items. Assessment activities will be conducted to monitor the children's progress in understanding the taught materials. A final evaluation will assess the achievement of activity objectives and their impact on the early childhood learning enthusiasm in the Ranggi literacy community. This activity can increase students' understanding of cultural diversity, strengthen their sense of nationality, encourage active participation in community service activities, and develop social and intercultural skills.